Identifying enhancers of innate immune signaling as broad-spectrum antivirals active against emerging viruses - Maarifi, Ghizlane; Martin, Marie-France; Zebboudj, Abderezak; Boulay, Aude; Nouaux, Pierre; Fernandez, Juliette; Lagisquet, Justine; Garcin, Dominique; Gaudin, Raphael; Arhel, Nathalie J; Nisole, Sébastien (Cell chemical biology, 2022)
The increasingly frequent outbreaks of pathogenic viruses have underlined the urgent need to improve our arsenal of antivirals that can be deployed for future pandemics. Innate immunity is a powerful first line of defense against pathogens, and compounds that boost the innate response have high potential to act as broad-spectrum antivirals. Here, we harnessed localization-dependent protein-complementation assays (called Alpha Centauri) to measure the nuclear translocation of interferon regulatory factors (IRFs), thus providing a readout of innate immune activation following viral infection that is applicable to high-throughput screening of immunomodulatory molecules. As proof of concept, we screened a library of kinase inhibitors on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and identified Gilteritinib as a powerful enhancer of innate responses to viral infection. This immunostimulatory activity of Gilteritinib was found to be dependent on the AXL-IRF7 axis and results in a broad and potent antiviral activity against unrelated RNA viruses.